The use and perception of urban green spaces through the twentieth century: a case study of the Rondebosch Common - Woelk, Michaela (Department of Environmental and Geographical Science, 2018)
The aim of this research was to unpack and analyse the emergence of narratives around urban green spaces as sites of community interaction, social activity and cultural and conservational value. I used the case study of the Rondebosch Common in Cape Town, South Africa during the period 1900 to 2015 to accomplish these aims. The Rondebosch Common has been fixture of the southern suburbs of the city for over one hundred years and provided a public green space for community interactions. I was able to gather letters and memos sent and received from the Town Clerk's Office from the South African National Archives Repository in Cape Town as well as newspaper articles from the Cape Argus and Cape News newspapers. The archival materials were chosen because they provided the point of view of the local government, the residents of Rondebosch and other users of the Rondebosch Common during the twentieth century. The newspaper articles were used to understand these points of views in the twenty-first century. Public spaces such as the Rondebosch Common are constructed in different ways, i.e. socially, politically, and these constructions determine the appropriate behaviours for the spaces as well as the values and meanings attributed to them. A public open green space such as the Rondebosch Common, which has existed as such for so long, provides an opportunity to examine the inherent political and social nature of old green spaces within the Global South context. Cape Town's colonial and apartheid state added a tension to interactions in the twentieth century as well as a layer of aspiration towards the English or Western ideal. The post-apartheid Cape Town urban and suburban landscape is still fraught with racial and socio-economic divisions. The purpose of my research was to determine how socio-economic, political and ideological context of the Rondebosch Common, in terms of both its physical location and the historical time period, has affected the way in which has been perceived by various groups and how it has been contested by those groups. I also attempt to unpack some of the uses of the Rondebosch Common and how and why they changed over time. It is argued that the demands and claims placed over a public green space such as the Rondebosch Common are represented over broader issues such as belonging, identity and civic entitlements (Di Masso, 2012).